Mexico Financial Sector Assessment Program : Sistema de pagos Electonicos Interbancarios -- Assessment of Observance of the CPMI-IOSCO Principles for Financial Market Infrastructure - World Bank Group (World Bank, Washington, DC, 2017)
The Sistema de Pagos Electrónicos Interbancarios (SPEI) is an important pillar of a complex payment and securities settlement infrastructure, through which the payments of various markets are settled with finality. In 2015, SPEI processed transactions for the equivalent of 10 times the country’s gross domestic product (GDP). It is supported by well-founded legal basis, and sound governance arrangements. It has developed a comprehensive risk management approach with an emphasis on operational risk management. At the same time, a few areas and opportunities for improvement have been noted in this report in light of enhancing principles for financial market infrastructures (PFMI) observance. This assessment was undertaken in the context of the International Monetary Fund (IMF) - World Bank (WB) financial sector assessment program (FSAP) to Mexico in April and May 2016. The objective of the assessment has been to identify potential risks related to the FMI that may affect financial stability. While safe and efficient FMIs contribute to maintaining and promoting financial stability and economic growth, they may also concentrate risk. If not properly managed, FMIs can be sources of financial shocks, such as liquidity dislocations and credit losses, or a major channel through which these shocks are transmitted across domestic and international financial markets.